Depletion of Ribosomal RNA Sequences from Single‐Cell RNA‐Sequencing Library. Issue 1 (1st July 2016) - Fang, Nan; Akinci‐Tolun, Rumeysa
Abstract: Recent advances in single‐cell RNA sequencing technologies have revealed high heterogeneity of gene expression profiles in individual cells. However, most current single‐cell RNA‐seq methods use oligo‐dT priming in the reverse transcription steps and detect only polyA‐positive for more accuracy, since there are also polyA‐positive non‐coding RNAs transcripts, not other important RNA species, such as polyA‐negative noncoding RNA. Reverse transcription using random oligos enables detection of not only the noncoding RNA species without polyA tails, but also ribosomal RNA (rRNA). rRNA comprises more than 90% of the total RNA and should be depleted from the RNA‐seq library to ensure efficient usage of the sequencing capacity. Commonly used hybridization‐based rRNA depletion methods can preserve noncoding RNA in the standard RNA‐seq library. However, such rRNA depletion methods require high input amounts of total RNA and do not work at the single‐cell level or with limited input DNA. This unit describes a novel procedure for RNA‐seq library construction from single cells or a minimal amount of RNA. A thermostable duplex‐specific nuclease is used in this method to effectively remove ribosomal RNA sequences following whole‐transcriptome amplification and sequencing library construction. © 2016 by John Wiley & Sons, Inc.